Predictive Value of N-Terminal Prohormone of Brain Natriuretic Peptide in Long-Term Remodeling of the Left Ventricle in Diabetic Patients of Young and Middle Age With Acute Coronary Syndrome After Percutaneous Coronary Intervention - Z. Wang; E. A. Asaphyeva; T. I. Makeeva (Неотложная медицинская помощь, 2021)
Abstract. Recently, quantitative analysis of the level of the N-terminal prohormone of the brain naturetic peptide (NT-proBNP) has been widely used to diagnose heart failure (HF). A statistically significant correlation was found between the serum NT-proBNP concentration and HF stage. It was found that in patients with high cardiovascular risk, NT-proBNP has the highest predictive value in relation to mortality. In young and middle-aged patients with diabetes mellitus (DM) with myocardial infarction (MI) and stents of an infarct-associated artery, the frequency of unfavorable remodeling (UR) of the left ventricle (LV) in the long-term prognosis was studied. The frequency of atherosclerotic lesions of the coronary arteries (CA) in patients with diabetes in acute coronary syndrome (ACS) was determined, the results of echocardiographic parameters were presented in the follow-up dynamics, the value of serum NT-proBNP in predicting LV UR 12 months after myocardial infarction (MI) was determined.Aim of study. To assess the diagnostic capabilities of NT-proBNP in the long-term prediction of the development of LV infarction in patients with MI with diabetes in young and middle age after percutaneous coronary intervention (PCI).Design. Prospective controlled non-randomized trial. The patients were examined twice: on the first day of ACS after PCI with stenting of infarct-associated coronary artery and 12 months after AMI. The study included 191 patients with ACS with / without ST-segment elevation, who were divided into two groups. The main group included 76 patients with ACS with diabetes mellitus, the comparison group included 115 patients with ACS without diabetes mellitus. Patients in both groups were comparable in age, gender, comorbidity, and complications of AMI. The duration of diabetes was, on average, 6 years (from one to 12 years).Material and methods. All patients underwent electrocardiography, echocardiography, tests for the content of troponin I, NT-proBNP, glycosylated hemoglobin, lipids, determined the level of creatinine in the blood and the glomerular filtration rate according to the Modification of diet in renal disease (MDRD). All patients were examined twice: on the first day of ACS after PCI with stenting of infarct-associated coronary artery and 12 months later.Results. In 69% of diabetic patients with anterior myocardial infarction and in 63% of patients with posterolateral MI 12 months after PCI, signs of LV inferiority were revealed in the form of an increase in the indices of end-diastolic and systolic volumes of the LV and low ejection fraction (≤45%). In patients without diabetes, these figures were 18% and 31%, respectively. High concentrations of NT-proBNP on the first day of myocardial infarction after PCI were of the greatest value in the diagnosis and prognosis of LV UR after 12 months.Conclusion. The NT-proBNP level of more than 776 pg/ml on the first day after PCI is an indicator of an unfavorable long-term prognosis in patients with young and middle-aged diabetes in terms of the development of LV systolic dysfunction.